Hubungan Efek Samping Kemoterapi Dengan Kualitas Hidup Pasien Kanker Di Rs Pku Muhammadiyah Gamping - Nanik Setiawati Ningrum; Lutfi Nurdian Asnindari; Sigit Harun (CV. ITTC INDONESIA, 2026)
Background: Cancer is the leading cause of death worldwide and is a serious health problem in Indonesia. Chemotherapy, as the main treatment, often causes side effects that affect patients' overall quality of life. This study aims to determine the relationship between chemotherapy side effects and the quality of life of cancer patients at PKU Muhammadiyah Hospital in Gamping, Yogyakarta. Using a quantitative method with a correlational descriptive design and a cross-sectional approach, 66 respondents were selected using purposive sampling. The research instruments used were demographic questionnaires, chemotherapy side effect questionnaires, and WHOQOL-BREF. Data analysis using the Kendall Tau correlation test showed that the majority of side effects were in the severe category (48.5%) and quality of life in the moderate category (59.1%). The correlation test results showed a significant relationship between chemotherapy side effects and quality of life in cancer patients with a p-value of 0.000 and a correlation coefficient of 0.531, indicating a fairly strong relationship. It was concluded that there was a relationship between chemotherapy side effects and the quality of life of cancer patients at PKU Muhammadiyah Gamping Hospital, where the more severe the side effects, the lower the quality of life. It is recommended that holistic support be provided by health workers and families to help patients cope with side effects so that their quality of life can be improved.